Model Pembelajaran Project Based Learning dalam Menciptakan Karya Tari di Kelas X.TITL 2 SMK Negeri 2 Wonosobo - Maharani, Syalaisha; Kusumastuti, Eny (Dinasti Research, 2025)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in the process of creating creative dance in class X.TITL 2 at SMK Negeri 2 Wonosobo. The research uses a descriptive qualitative method, with data collected through observation, interviews, and documentation. The results show that the learning process begins with a pre-instructional planning stage in the form of a teaching module designed according to school facilities and aligned with the Merdeka Curriculum. The application of the PjBL model successfully enhances students' active participation, creativity, and problem-solving skills through collaborative group work. Although the resulting dance works still require further development in terms of creativity, the learning process is effective. Project-based learning provides meaningful learning experiences and encourages students to be more independent and collaborative. Therefore, full support from the school and continuous development of the method by teachers are necessary to optimize learning outcomes.